Study on Russian Botanical Garden construction characteristics – on the example of Russia Northern-West botanical gardens. Issue 1 (June 2021) - Budilovskaia, A; Shao, Y
Abstract: Botanical garden is an important symbol of modern urban civilization. The botanical garden not only protects the ecological environment, but also increases the urban green space area and improves the urban environment and quality of life. This paper analyses and summarizes the construction of 12 botanical gardens of the northwest European part of Russia from three aspects: regional, cultural and plant's characteristics. What's more, analysing its spatial layout, concludes that it is mainly affected by the existing natural characteristics and cultural diversity. The purpose of this study is to provide reference for the development and construction of botanical garden in China.